Multilevel Investigation of Leadership Prototype Perception: Political Behavior in Relation to Effectiveness and Trust - Arslan Aykut; Yener Serdar; Korkmaz Fatma; Erogul Murat Sakir (Organizacija)
Empirical evidence suggests that a leader’s political skills may act as a moderator that might decrease the effect of prototypicality’s impact on trust and on leadership effectiveness. The study investigated leading political skills as second-level regulatory variables in connection to leader effectiveness and trust with the purpose of testing a cross-level moderated mediation model within a traditionally collectivist culture like Turkey in efforts to contextualize and expand understanding of leadership prototype perception.